Answer:
x ≤ -6
Explanation:
Distribute 3 through the paraentheses:
3(x - 6) + 2 ≥ 5x - 4
↓
3x - 18 + 2 ≥ 5x - 4
Calculate the sum:
3x - 18 + 2 ≥ 5x - 4
↓
3x - 16 ≥ 5x - 4
Move the variable (5x) to the left-hand side and change its sign:
3x - 16 ≥ 5x - 4
↓
3x -5x - 16 ≥ - 4
Move the constant (- 16) to the right-hand side and change its sign:
3x -5x - 16 ≥ - 4
↓
3x - 5x ≥ - 4 + 16
Collect like terms (3x and - 5x):
3x - 5x ≥ - 4 + 16
↓
-2x ≥ - 4 + 16
Calculate the sum:
-2x ≥ - 4 + 16
↓
-2x ≥ 12
Divide both sides of the inequality by -2 and flip the inequality sign:
x ≤ -6